New approach to estimating variability in visual field data using an image processing technique. Issue 3 (March 1995) - Crabb, D P; Edgar, D F; Fitzke, F W; McNaught, A I; Wynn, H P
Abstract : AIMS--A new framework for evaluating pointwise sensitivity variation in computerised visual field data is demonstrated. METHODS--A measure of local spatial variability (LSV) is generated using an image processing technique. Fifty five eyes from a sample of normal and glaucomatous subjects, examined on the Humphrey field analyser (HFA), were used to illustrate the method. RESULTS--Significant correlation between LSV and conventional estimates--namely, HFA pattern standard deviation and short term fluctuation, were found. CONCLUSION--LSV is not dependent on normals' reference data or repeated threshold determinations, thus potentially reducing test time. Also, the illustrated pointwise maps of LSV could provide a method for identifying areas of fluctuation commonly found in early glaucomatous field loss.